Local and global in the formation of a learning theorist: Peter Jarvis and adult education - Holford, John (Taylor & Francis, 2017)
Peter Jarvis is a towering figure in the study of adult and lifelong education and a leading and original theorist of learning. This paper sets out his intellectual and professional biography, maps the main contours of his work and introduces fourteen papers by leading scholars devoted to his work. Five broad phases in Jarvis’ life are identified: (a) youth, self-education, Methodist ministry and early teaching and research; (b) founding of the International Journal of Lifelong Education, authorship of important textbooks on adult and professional education and linking of academic communities in different countries; (c) early research on and theorisation of learning; (d) engagement from the early 1990s with debates on lifelong learning and the learning society; and (e) return to theorisation of learning, particularly from the perspective of globalisation, from around 2000. Recurring themes include ethics and responsibility, the essentially social nature of learning, democracy, and authenticity in human relationships.